Change in Plasma ATN Biomarkers Over a 12‐Week Physical Activity Intervention Among Older African Americans: Program for African American Cognition and Exercise (PAACE). (20th December 2022) - Carmichael, Owen T.; Gwizdala, Kathryn L.; Brouillette, Robert; Beyl, Robbie; Johnson, William; Hebert, Callie; Carter, Leah; Harris, Melissa; Newton, Robert L
Abstract: Background: Plasma markers of amyloid, tau, and neurodegeneration (ATN) are promising as correlates of AD biological and clinical features, but data from older African Americans, and data on change during non‐pharmacological interventions, is limited. Method: The Program for African American Cognition and Exercise (PAACE) randomized older cognitively normal African American adults into a 12‐week successful aging group (SAG) to attend educational sessions or a 12‐week physical activity group (PAG) to complete supervised and in‐home physical activity. The Repeatable Battery for the Assessment of Neuropsychological Status (RBANS) and cardiometabolic risks were assessed pre‐ and post‐intervention. The Quanterix Simoa® Neuro 4‐Plex E and pTau‐181 Advantage Kits were used to measure plasma concentrations of amyloid beta (ABeta) 1‐40 and 1‐42, glial fibrillary acidic protein (GFAP), neurofilament light (NfL), and tau protein phosphorylated at threonine 181 (pTau‐181). Linear mixed effects regression models assessed modifiers of change in plasma and RBANS measures. Result: A set of 54 PAACE completers aged 69.3 +/‐ 3.4 years (40 female, 14 male) provided non‐outlier measurements. ABeta 1‐40 decreased ( p =.027), and RBANS global cognition, visuospatial, and delayed memory scores increased, over the intervention (maximum p value: .040). Plasma ATN biomarkers did not differ between SAG and PAG at baseline, but SAG did have greater declines in pTau‐181 than PAG did ( p =.003, Figures 1‐2), and women had greater declines in pTau‐181 than men did ( p = .045, Figure 3). Greater age was associated with greater ABeta 1‐40, ABeta 1‐42, GFAP, and NFL (maximum p = .008). Greater diastolic blood pressure was associated with lesser NFL ( p = .021) and ABeta 1‐40 ( p = .041). Greater GFAP, NfL, and pTau‐181, suggestive of greater burden of tau and neurodegeneration, were associated with lesser RBANS language score (maximum p = 0495). Greater pTau‐181 was associated with lesser RBANS immediate memory score ( p = .035). Plasma ATN markers did not modify pre‐to‐post‐intervention change in any RBANS summary score (minimum p =.10). Conclusion: Among cognitively normal older African Americans, change in plasma ATN biomarkers over the course of a nonpharmacological intervention differed by study group and gender. The markers differed by cardiometabolic risks and associated with cognitive function in an intuitive fashion.